2008
DOI: 10.1128/mcb.00431-08
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Hsp27, a Novel Subunit of AUF1 Protein Complexes, Functions in AU-Rich Element-Mediated mRNA Decay

Abstract: Controlled, transient cytokine production by monocytes depends heavily upon rapid mRNA degradation, conferred by 3 untranslated region-localized AU-rich elements (AREs) that associate with RNA-binding proteins. The ARE-binding protein AUF1 forms a complex with cap-dependent translation initiation factors and heat shock proteins to attract the mRNA degradation machinery. We refer to this protein assembly as the AUF1-and signal transduction-regulated complex, ASTRC. Rapid degradation of ARE-bearing mRNAs (AREmRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 61 publications
6
96
0
Order By: Relevance
“…Our observation is consistent with previous findings where HSP27 is able to prevent cells from apoptosis by interacting with Cyto C (23) or by interfering the apoptotic signaling upstream of the mitochondrial Cyto C release (24,25). In addition, it was reported that HSP27 as a subunit of AUF1 protein complexes can also act as a RNA-binding protein to mediate mRNA decay (26). Enhanced HSP27 expression in response to oxidative stress binds to the 3 0 -untranslated region of BIM mRNA to repress its translation and subsequently prevent neuronal death in cerebellar granule neurons (27).…”
Section: Discussionsupporting
confidence: 82%
“…Our observation is consistent with previous findings where HSP27 is able to prevent cells from apoptosis by interacting with Cyto C (23) or by interfering the apoptotic signaling upstream of the mitochondrial Cyto C release (24,25). In addition, it was reported that HSP27 as a subunit of AUF1 protein complexes can also act as a RNA-binding protein to mediate mRNA decay (26). Enhanced HSP27 expression in response to oxidative stress binds to the 3 0 -untranslated region of BIM mRNA to repress its translation and subsequently prevent neuronal death in cerebellar granule neurons (27).…”
Section: Discussionsupporting
confidence: 82%
“…AREs are instability motifs found within the 3Ј untranslated region of some transcripts and serve as markers for rapid degradation. Recently published research has shown that knockdown of Hsp27 (all forms) resulted in decreased mRNA decay (29). During HSV-1 infection, although most cellular mRNAs are degraded through the activity of the viral vhs (virion host shutoff) protein (27), some, like that of the cytokine regulator IEX-1, are stabilized (15).…”
Section: Hsp27 Modification During Hsv-1 Infection (I)mentioning
confidence: 99%
“…AUF1 consists of four isoforms of 37, 40, 42, and 45 kDa generated by alternative pre-mRNA splicing of a single pre-mRNA. They associate with heat shock proteins Hsc70-Hsp70 and Hsp27, translation initiation factor eIF4G, poly(A)-binding protein (PABP), and other unidentified proteins to form a multisubunit complex we refer to as AUF1-and signal transduction-regulated complex (ASTRC) (15,27). This complex recruits messenger ribonucleases to degrade ARE mRNAs.…”
mentioning
confidence: 99%
“…This complex recruits messenger ribonucleases to degrade ARE mRNAs. RNA interference (RNAi)-mediated knockdown of either AUF1 or Hsp27 stabilizes TNF-␣ ARE mRNA, indicating that both proteins are essential for ARE-mediated mRNA degradation (AMD) (27).…”
mentioning
confidence: 99%